2011
DOI: 10.1152/ajpendo.00048.2011
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates metabolic disorders and muscle wasting in streptozotocin-induced diabetic rats

Abstract: Diabetes mellitus (DM) is characterized by dysregulated energy metabolism. Resveratrol (RSV) has been shown to ameliorate hyperglycemia and hyperlipidemia in diabetic animals. However, its overall in vivo effects on energy metabolism and the underlying mechanism require further investigation. In the present study, electrospray ionization-tandem mass spectrometry was employed to characterize the urine and plasma metabolomes of control, streptozotocin-induced DM and RSV-treated DM rats. Using principal component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 51 publications
3
63
0
1
Order By: Relevance
“…In this regard, RSV was delivered systemically to live animals and thus its positive effects on muscle stem cells could be indirect, e.g. via the global improvement in energy metabolism and reduced protein degradation, which have been reported in a rat STZ model [28]. Regardless of a precise molecular mechanism, from a clinical perspective this work uncovers a novel strategy for improving the regenerative performance of organ stem cells in type I diabetes.…”
Section: Discussionmentioning
confidence: 87%
“…In this regard, RSV was delivered systemically to live animals and thus its positive effects on muscle stem cells could be indirect, e.g. via the global improvement in energy metabolism and reduced protein degradation, which have been reported in a rat STZ model [28]. Regardless of a precise molecular mechanism, from a clinical perspective this work uncovers a novel strategy for improving the regenerative performance of organ stem cells in type I diabetes.…”
Section: Discussionmentioning
confidence: 87%
“…These similarities also mean that the lack of improvement in cardiac function and glucose levels observed in the STZ + Res animals was not so unexpected. Ultimately, there is insufficient evidence to fully support the viability of resveratrol as a nutritional supplement to improve metabolic health (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66) .…”
Section: Discussionmentioning
confidence: 99%
“…Rsv has been reported to possess a host of biological effects due probably to its antioxidant nature [22,23,24] and its effect on energy metabolism. Studies with non-neural organs such as rat heart and kidney have demonstrated the ability of Rsv to reduce ischemia/reperfusion injuries [25,26].…”
Section: Introductionmentioning
confidence: 99%